Islamic Boarding School Education as a ‎National Multicultural Education Role Model - St. Rodliyah (State Islamic Institute of Madura, 2022)
Pesantren is an institution that has inherited the nation's values, culture, and character, so it has a significant role in preserving multicultural values ​​to build the unity and integrity of the Indonesian nation. This study aims to reveal the implementation of multicultural education in Islamic boarding schools as a commitment to maintaining and respecting ethnic, ethnic, and cultural diversity. This study uses a qualitative approach with the type of library research so that the data source comes from literature, books, and scientific articles. The results of this study indicate that the education system implemented in Islamic boarding schools has characteristics compared to public educational institutions. The educational values ​​carried are also in line with and uphold the values ​​of multicultural education as a manifestation of the life view of the pesantren community. Pesantren education, full of multicultural values, ​​can be used as a role model for national education because the education applied in pesantren contains fundamental values ​​in multicultural education. In addition, Islamic boarding school education is not only oriented to cognition, where knowledge and intellectuality are the main orientations in the educational paradigm. Instead, it emphasizes the development of human beings who have character, morality, human values, compassion, courtesy, and peace. The existence of diverse santri requires that the pesantren environment be designed inclusively by upholding the value of diversity and difference. A culture of mutual respect and respect for differences is an important thing to do in order to avoid the potential for significant conflicts on racial issues.